2017
DOI: 10.1111/echo.13735
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic assessment of Perceval sutureless bioprosthesis by dobutamine stress echocardiography

Abstract: Objectives:The aim of this study was to evaluate the hemodynamic performance of a sutureless bioprosthesis under high workload at mid-term follow-up. Methods:Thirty-two patients who underwent isolated aortic valve replacement with a Perceval sutureless bioprosthesis with a minimum follow-up of 1 year were enrolled in this study. S size prosthesis was deployed in 10 patients (31.3%), M size in 9 (28.1%), L size in 8 (25%) and XL size in 5 (15.6%). Effective orifice area (EOA), EOA index (EOAi), and transvalvula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This double sheet of the Perceval could lead to less leaflet mobility, especially at rest, when the stroke volume is not very high. This prosthesis has been shown to dramatically increase its opening during the exercise [ 11 ]. Thus, our findings could change in the presence of high demand for cardiac output.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This double sheet of the Perceval could lead to less leaflet mobility, especially at rest, when the stroke volume is not very high. This prosthesis has been shown to dramatically increase its opening during the exercise [ 11 ]. Thus, our findings could change in the presence of high demand for cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous meta-analyses, the lower rate of moderate PPM using the Trifecta could have a benefit in some specific groups such as young patients or those with left ventricular dysfunction. The Perceval aortic prosthesis has shown to dramatically increase its opening during the exercise [ 11 ]. Thus, our findings could change in the presence of high demand for cardiac output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Furthermore, Rubino et al showed that under stress, Perceval size S had the highest increase of EOA index at a mean follow-up of 19.5 months, and this benefit was also observed in those patients with severe PPM. 31 Finally, an in vitro study by Tasca et al demonstrated that Perceval shows the greatest EOA when compared with other stented valves on small annuli. 32 These results are probably related to its stentless property.…”
Section: Discussionmentioning
confidence: 99%
“…2 As standard AVR is associated with high rates of morbidity in these patients, in the last few years, rapid-deployment aortic valves (RDV) have been developed to facilitate surgical methods, reduce aortic cross-clamping and cardiopulmonary bypass (CPB) time and curtail the risk of mortality and morbidity, and to maintain satisfactory hemodynamic outcomes and low periprosthetic leak rates. 3,4 Several studies confirmed how RDV has been widely used even in off-label indications such as with concomitant mitral valve surgery, 5 surgery for endocarditis, 6 isolated aortic regurgitation 7 and may also be an alternative for high-risk patients. 8 In this study, we compared the mid-term outcomes of rapid-deployment AVR (RD-AVR) with those of the conventional procedure in high-risk surgical patients who underwent isolated AVR or with other cardiac procedures.…”
mentioning
confidence: 96%